An Assessment of Dental Practitioners’ Pain and Evidence-Based Physical and Management Strategies: A Literature Review - Arciszewski, Kamil; Stenzel, Paweł; Niewola, Karolina; Szumiło, Jakub; Kasperska, Klaudia; Walczak, Dominika; Orda, Karolina; Hariasz, Natalia; Markiv, Mariana; Słowik, Michał (Quality in Sport, 2026)
Background. Dentistry is a highly demanding profession that requires specific physical postures during clinical procedures. The prolonged adherence to such postures throughout a practitioner’s career can lead to musculoskeletal discomfort and chronic pain. These physical and ergonomic challenges may contribute to occupational burnout and reduced job satisfaction. Aim. The aim of this study is to identify the most prevalent sites of musculoskeletal at dentists and to discuss evidence-based strategies for alleviating such discomfort, with the ultimate objective of enhancing occupational longevity in the dental workforce. Material and methods. A systematic search of high-quality academic databases was conducted to identify peer-reviewed studies reporting statistical data and clinical management strategies related to the most prevalent musculoskeletal disorders among dental professionals. From the initial pool of literature, 56 studies - comprising randomized controlled trials, systematic reviews, and clinical studies - were selected for the further and more precise review and selected to discuss in this paper. Results. Mostly cited musculoskeletal disorders among dental professionals include neck pain, low back pain, hip pain, shoulder pain, and forearm and wrist pain, with carpal tunnel syndrome and forearm discomfort. For neck pain, evidence-based recommendations are manual therapy and therapeutic exercise programs, which have demonstrated efficacy in reducing pain and improving function. Low-back and hip pain are best addressed through mind-body and core-stabilizing interventions: tai chi, yoga, and Pilates, as well as core-based or stabilization exercises, which enhance postural control and reduce mechanical stress. In the case of shoulder pain, treatment protocols suggest a combination of stretching exercises and radiofrequency ablation. In Forearm pain and carpal tunnel syndrome, a multimodal approach is recommended.